Agrochemical Usage Inventory and Measured Residues in Streams Within an Off-Season Durian Production Region of Thailand - Panatda Pibul; Siriuma Jawjit (Frontiers in Sustainable Food Systems, 2021)
Rising demand for off-season durian production in Thailand has led to increased agrichemical use and potential environmental and health concerns. In this study, we surveyed 117 farmers and collected water samples from 11 villages in Krungching Sub-district. Overall, 108 agrochemicals were listed as being used in off-season durian production, but we focused on residual concentrations of the persistent herbicides glyphosate and paraquat in surface water. We applied a pollution release and transfer registry for 2016 to determine an application rate of 288,149 kg/year for these agrichemicals. These were primarily detected during the dry season, and not the wet season. This reporting system can be used to develop seasonal environmental surveillance and monitoring tools for more sustainable use of agrochemical substances in off-season durian production in environmentally sensitive areas such as the Krungching River watershed, especially during the first stage of cultivation (dry season), in order to ensure the use of agricultural chemicals under appropriate circumstances. Further studies are needed to better understand the full diversity of persistent agrochemical substance usage and disposal, in order to reorient agricultural activities to focus on local needs and capabilities as part of efforts to implement more sustainable agriculture in Thailand.